Quantifying Compositional Homogeneity in Pb(Zr, Ti)O3 Using Atom Probe Tomography. Issue 9 (29th July 2014) - Kirchhofer, Rita; Diercks, David R.; Gorman, Brian P.; Ihlefeld, Jon F.; Kotula, Paul G.; Shelton, Christopher T.; Brennecka, Geoff L.; Green, D. J.
<x xml:space="preserve">Abstract</x> Atom probe tomography (APT) is a powerful materials characterization technique capable of ppm chemical resolution and near atomic scale spatial resolution. However, owing to a number of factors, the technique has not been widely applied to insulating materials and even less to complex oxides. In this study, we outline the methodology necessary to obtain high‐quality results on a technologically relevant complex oxide Pb(Zr, Ti)O3 (or PZT) using laser‐assisted APT on both bulk and thin film specimens. We show how, with optimized and well‐controlled conditions, APT complements conventional techniques such as STEM‐EDS. The correlative information can be used to obtain the nanoscale 3‐D chemical information and investigate the nanoscale distribution of cations. Using nearest‐neighbor cluster analysis routines, 5–10 nm segregation of B‐site cations was detected in bulk sintered PZT 53/47 from chemically prepared powders. No statistically significant segregation of B‐site cations was observed in thin film specimens. This work opens new avenues toward understanding the process‐structure properties in complex materials at length scales heretofore unachievable.